Large-Scale FDM 3D Printing in 6 Degrees of Freedom on One ARM KUKA KR 60 - Chicoma, Max Uriarte (2022)
3D printing is widely used due to its versatility and low manufacturing cost, but this manufacturing method has limitations such as the use of only 3 degrees of freedom that consists of extrusion by layers contained in the XY plane with displacement high on the Z-axis. On the other hand, there is the printing volume which is reduced, and finally the loss of material that occurs when having supports. Next, a versatile procedure is presented, which is mounted on a KUKA KR60 robotic arm, with which complex surfaces can be printed and of a larger size with the help of the robot arm's work area, parts with concave surfaces, and convex where printing supports are removed. This proposal intended to have a printer mounted on a KUKA KR60 robotic arm with which you can have 6 degrees of freedom, and use approximately the cubic meter of freedom that the arm has. This achieves prints with greater complexity and volume of approximately 1 m3, in addition to being able to eliminate the waste of material that occurs in conventional 3D printing. Also, in parallel, it is possible to generate the codes for a generic printing plate that is compatible with G-CODE and for the robotic arm module.